Mechanical, structural and nuclear radiation shielding competencies of some tellurite glasses reinforced with molybdenum trioxide. (8th February 2021) - El-Denglawey, A; Issa, Shams A M; Saddeek, Yasser B; Elshami, Wiam; Sayed, M A; Elsaman, Reda; Tarhan, N; Tekin, H O
Abstract: In this study, a group of molybdenum boro-tellurite glass samples and their mechanical parameters and nuclear radiation shielding competencies were investigated. The amorphous structures of molybdenum boro-tellurite glasses were confirmed by XRD patterns. Synergistic positive effect of MoO3 reinforcement on gamma ray attenuation properties and mechanical parameters was investigated. For this aim, and in the energy range 0.015–15 MeV, the mass attenuation coefficients (MAC) had been computed by computational methods. At 0.015 MeV, the MAC values increase from 28.06 to 33.25 (cm 2 g−1 ) as the MoO3 content increases from 0 to 30 mol %, while the half value layer values decrease from 4.84 to 3.88 (cm) at 15 MeV. The longitudinal ultrasonic velocity (VL ) and shear ultrasonic velocity (VS ), longitudinal modulus (L), shear modulus (S), bulk modulus (K), and Young's modulus (Y) increase from 3450 to 3637 (m s −1 ), from 1994 to 2146 (m s −1 ), from 53.44 to 64.88 (GPa), from 17.86 to 22.58 (GPa), from 29.63 to 34.77 (GPa), and from 44.61 to 55.69 (GPa), respectively. The analysis of the shielding and mechanical indicates best protection of the explored glasses for γ -irradiation. Based on the analysis, the glass 30MoO3 -70TeO2 with the maximum MoO3 addition indicated best γ -irradiation protection and mechanical parameters among the explored glasses.